"Baby, you can drive my car": Psychological antecedents that drive consumers' adoption of AI-powered autonomous vehicles. (January 2022) - Meyer-Waarden, Lars; Cloarec, Julien
Abstract: Artificial intelligence (AI)-powered autonomous vehicles (AVs) are one of the most highly anticipated technological advancements of our time, with potentially wide-ranging social implications in terms of driver/passenger safety, equity and environmental aspects. However, most consumers feel reluctant towards the adoption of AI-powered AVs. To analyse user acceptance of AI-powered AVs, we need to understand the related psychological, social and cognitive factors. To do so, we established a conceptual model based on the technology acceptance literature and considered how performance and effort expectancy, social recognition, hedonism technology security and privacy concerns influence both technology trust and user well-being as mediators that subsequently influence the behavioural intention of the use of AI-powered AVs. We used user innovativeness as a moderator, and we performed a survey in France. Our results from the structural equation modelling largely support the positive relationship between the behavioural intention to use AI-powered AVs and performance-/effort expectancy, social recognition, well-being, hedonism and technology trust, as well as security. On the other hand, privacy concerns negatively influence technology trust. Graphical abstract: Image 1 Highlights: Few studies focused on antecedents of behavioral intention to use (BIU) of AI-powered autonomous vehicles' (AV). Results suggest focusing on AVs' driver well-being, hedonism and social recognition to increase BIU. It is important to increase both AV technology security and trust to raise BIU. Data collected by AV should be carefully managed to decrease privacy concerns that negatively influence BIU.